eIF5A binds to translational machinery components and affects translation in yeast - Zanelli, Cleslei Fernando [UNESP]; Maragno, Ana L. C.; Gregio, Ana P. B.; Komili, Suzanne; Pandolfi, Jose R.; Mestriner, Carlos A.; Lustri, Wilton R.; Valentini, Sandro Roberto [UNESP] (Elsevier B.V., 2006)
The putative translation factor eIF5A is essential for cell viability and is highly conserved from archebacteria to mammals. Although this protein was originally identified as a translation initiation factor, subsequent experiments did not support a role for eIF5A in general translation. In this work, we demonstrate that eIF-5A interacts with structural components of the 80S ribosome, as well as with the translation elongation factor 2 (eEF2). Moreover, eIF5A is further shown to cofractionate with monosomes in a translation-dependent manner. Finally, eIF5A mutants show altered polysome profiles and are sensitive to translation inhibitors. Our results re-establish a function for eIF5A in translation and suggest a role for this factor in translation elongation instead of translation initiation. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: eIF5A; ribosome; translation; eEF2; P0; L11; hypusine; protein synthesis